Is There Something Worthwhile in Somethingism? - Gan, Peter (European journal for philosophy of religion, 2022)
Although ietsism, which comes from a Dutch term referring to "somethingism," came on the religious scene a couple of decades ago, Anglophone publications springing from serious reflections on this term have only just recently appeared. This paper constitutes an attempt at addressing a couple of questions pertaining to this rather novel term. Two of these main questions concern the characteristics of ietsism that set it apart from other faith orientations, and the means by which ietsism is able to stand up to the test of its practical worth in terms of promising to fulfil a profound need in human life.